Does top management team diversity affect accounting quality? Empirical evidence from Germany - Felix Schumann; Toni W. Thun; Tobias Dauth; Henning Zülch (Journal of Management and Governance, 2023)
Earnings management decisions and ineffective monitoring activities have contributed to financial accounting scandals and reduced confidence in firms' reporting quality among potential investors, lenders and other creditors. The implementation of an effective top management team (TMT) is considered essential in this context. It is well known that top managers have considerable discretion over firms' financial reporting since they choose whether and how to manage earnings. However, research has yet to establish the relationship between top managers' diversity attributes and firms' earnings management levels. Therefore, this study analyses whether and how top managers' nationality, gender and age diversity are associated with accounting quality. Based on a sample of German DAX 30 listed firms from 2011 to 2018, we found that diversity in TMT nationality and gender have a positive impact on accounting quality. This relationship is context-dependent and negatively moderated by the tenure of the chief financial officer. Our findings provide novel insights on accounting quality for practitioners such as investors, regulators and stock corporations. The implications of this study further advance the academic debate on diversity in TMTs and its effects on earnings management.
Keywords: 650; Accounting quality; Corporate governance; Earnings management; Top management teams; Top management team diversity; Upper echelons theory